Predicting the Development of Analytical and Creative Abilities in Upper Elementary Grades. Issue 4 (2nd October 2017) - Gubbels, Joyce; Segers, Eliane; Verhoeven, Ludo
Abstract : In some models, intelligence has been described as a multidimensional construct comprising both analytical and creative abilities. In addition, intelligence is considered to be dynamic rather than static. A structural equation model was used to examine the predictive role of cognitive (visual short-term memory, verbal short-term memory, selective attention) and socio-emotional (motivation, self-concept, well-being) child characteristics in the development of analytical and creative abilities in 116 Dutch children over the course of 5th and 6th grade. Results showed increasing levels of both analytical and creative abilities over the grades with the 2 types of abilities developing more or less independently. The development of analytical abilities was predicted by visual and verbal short-term memory and self-concept, the development of creative abilities by visual short-term memory and well-being. These results show that analytical and creative abilities have highly independent developmental trajectories, each with specific cognitive and socio-emotional predictors.